Working conditions as one of the areas for implementing the concept of corporate social responsibility = Warunki pracy jako obszar urzeczywistniania koncepcji społecznej odpowiedzialności w przedsiębiorstwie - Cierniak-Emerych, Anna; Zięba, Kamil (Zielona Góra: Faculty of Economics and Management Press)
Implementation of the corporate social responsibility (CSR) concept is presented, as it applies to the practice of companies. The authors focus on an isolated area of CSR implementation, namely the improvement of working conditions, in the context of selected international standards and norms directly referencing the CSR concept.
Keywords: koncepcja CSR; warunki pracy; bezpieczeństwo i higiena pracy; CSR concept; working conditions; occupational health and safety